Cavitons - new fenomenon in the Earth's foreshock - Kajdič, Primož; Blanco-Cano, Xochitl; Omidi, Nojan; T. Russell, Christopher (Anali PAZU, 2022)
The region upstream of the earth's bow shock is highly turbulent. It is populated by fluctuations of plasma density and magnetic field. Besides the fluctuations known as waves, there are also transient structures, such as density holes, hot flow anomalies and foreshock cavities. The recent global hybrid (kinetic ions + fluid electrons) simulations results suggested the existence of a new type of transient structures called the foreschock cavitons. At first glimpse, the cavities and the cavitons share many similarities, but they form due to different physical processes. In this work we present the region upstream of the earth's shock, i.e. the earth's foreshock, and describe the properties of the most typical populations of particles, waves and transient structures that populate it. We compare in detail the observational properties of foreshock cavities and cavitons by presenting two case studies and we discuss their similarities and differences.
Keywords: magnetospheric physics; caviar in the area before the shock wave; caviar in the area before the shock waves